Actualization of Islamic Values in the Nyadran Tradition in Astono Temu Ireng Karanganom, Karanganyar - Kahfinda Kautsari (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2024)
Indonesia's diversity includes religion, ethnicity, customs, and culture. Various traditions are carried out in various circles of society. The nyadran tradition is one example of a form of local wisdom that is still preserved by the Javanese community. This is evident in various areas ahead of the month of Ramadan, the ritual is carried out a lot. Especially in Astono Temu Ireng Karanganom, Karanganyar which still preserves this tradition to this day. For the people of Karanganyar District, it is intended as a symbol of gratitude and as a means to be oriented to Allah Swt and also to pray for the ancestors. Nyadran is also used as a means to maintain a mutual cooperation lifestyle and maintain harmony. The purpose of the study was to determine the actualization of Islamic values in the nyadran tradition in Karanganyar District